Il gioco della verità. Imago naturae: un bambino che gioca - Rosi, Laura (Rivista Internazionale di Studi Leopardiani, 2021)
The essay analyzes the presence of the IV Bucolica by Virgilio and of the Misopogon by Giuliano within the Palinodia al marchese Gino Capponi (1835) as both relevant inner texts supporting Leopardi’s radical criticism to his contemporaries on the themes of society and education. The Palinodia has its core in the description of the child who builds and destroys little playhouses. This ancient picture has last through time, now representing a naturalistic parable which discloses the undeniable truth of the natural evil in the simplicity of a child’s game.